Simultaneous Estimation of Lamivudine, Zidovudine and Nevirapine by RP-HPLC in Pure and Pharmaceutical Dosage Form - Hari Krishnan, N.; Gunasekaran, V.; Roosewelt, C.; Kumar Meher, Vijaya; Kalaivani, K.; Ravichandiran, V. (Asian Journal of Chemistry, 2010)
A simple, accurate, precise and reproducible high performance liquid chromatographic method has been developed for the simultaneous estimation of lamivudine, zidovudine and nevirapine in pharmaceutical dosage forms. A Gemini ODS C18 column (4.6 mm × 25 cm i.d., 5 μm particle size) in isocratic mode, with mobile phase acetonitrile, orthophosphoric acid buffer (pH 3.5) and methanol (15:60:25) (v/v/v) the flow rate was 1 mL/min and effluent was monitored at 265 nm. The approximate retention time for lamivudine, zidovudine and nevirapine were 3.36, 5.30 and 9.28 min, respectively. The linearity for lamivudine, zidovudine and nevirapine was in the range of 36-84, 72-168 and 48- 112 μg/mL, respectively. Quantity found for lamivudine, zidovudine and nevirapine were 150.6, 298.11 and 199.12 mg, respectively. The percentage estimation of labeled claims of lamivudine, zidovudine and nevirapine from marketed tablet was found to be 100.40, 99.37 and 99.55, respectively. The method was validated in terms of accuracy, precision, specificity and ruggedness. The addition of known quantity of standard drugs in the pre-analyzed test solution percentage recovery was calculated in each case. The percentage recoveries obtained for lamivudine, zidovudine and nevirapine were found within the range of 98.62-99.88 %. The proposed method is found to be accurate, precise, simple and rapid which can be used routinely for simultaneous estimation of proposed combination in tablet formulation.